Relation Between Macroeconomic and Agriculture Sector of Iran (Emphasize on Monetary Policy) - Amir Dadras Moghadam; Mansoor Zibaei (فصلنامه پژوهش‌های اقتصادی ایران, 2009)
The purpose of this study is to investigate the impact of monetary policy and exchange rate on agriculture supply, prices and exports of agricultural sector with VEC approach and impulse response functions. In this paper, variables are interest rate, exchange rate, monetary supply, inflation, agriculture output and input prices, agricultural supply and exports, income and the degree of openness from 1961 to 2005. The results show in order to decrease inflation, and control agriculture prices we must not emphasize on monetary policy but in the long-run exchange rate, financial, development and trade policy are most important factors in price stability policy. Results also indicate that changes in macroeconomic variables have an effect on the agricultural sector but the reverse effect does not hold.